Pengelolaan PENGELOLAAN MEDIA MENGGUNAKAN PENDEKATAN KONTEKSTUAL DALAM MENINGKATKAN MINAT BELAJAR PEMBELAJARAN PENJAS SMPIT KHAIRUNNAS KOTA BENGKULU: - - Citra Dewi Dewi; Rita Prima Bendriyanti; Febri Hariansyah (Jurnal Speed (Sport, Physical Education, Empowerment), 2022)
Management of learning media is part of efforts to improve the quality of education and learning in schools. With good management of learning media, it is expected to be able to increase interest in learning, learning outcomes and children's abilities in learning while the purpose of this study is to find out the right media management that can be used in physical education learning at SMPIT Khairunnas schools. Good learning can be in the form of pictures, videos and others to facilitate learning. One model of learning media to support and increase student interest that can be used in learning is contextual learning. Contextual learning model is a learning concept that helps teachers relate the material being taught to students' real world situations and conditions and further encourages students to make connections between their knowledge and its application in real life. This research uses descriptive qualitative research, data collection uses observation techniques, field observations. Keywords: Contextual Media Management.